The effect of the still‐face paradigm on infant behavior: A cross‐cultural comparison between mothers and fathers. (7th October 2019) - Li, Wei; Woudstra, Mi‐lan J.; Branger, Marjolein C. E.; Wang, Lamei; Alink, Lenneke R. A.; Mesman, Judi; Emmen, Rosanneke A. G.
Abstract: Most still‐face paradigm (SFP) studies have been done in Western families with infant–mother dyads. The present study investigated the SFP pattern in 123 Dutch and 63 Chinese 4‐month‐old infants with mothers and fathers. The classic SFP effect was found for positive affect and gaze in both countries. For negative affect, Chinese infants showed a different SFP pattern than Dutch infants. With fathers, infants displayed a less pronounced SFP pattern for positive affect and an increase from the still face to the reunion for negative affect. Only a minority of infants showed the expected SFP pattern across episodes. Our findings support that infant emotion expression is influenced by parent gender and cultural context. An interesting avenue for further study is the exploration of the origins of within‐ and between‐gender and culture differences in affective communication between parents and infants.